Profil keterampilan kolaborasi siswa SMA pada praktikum maya sistem ekskresi - Junita, Astrid; Supriatno, Bambang; Purwianingsih, Widi (Assimilation: Indonesian Journal of Biology Education, 2021)
This study aims to analyze high school students’ collaboration skills in an excretion system virtual lab work about detection of sugar in urine. This study also revealed students’ responses regarding virtual lab work learning. Research method used here is descriptive method. The study was conducted on 35 students in one class of 11th science grade from a public senior high school in Bandung city, that obtained by purposive sampling technique. Data were collected with non-test instruments in form of observation sheet as the main data source and worksheet, peer assessment sheet, and questionnaire as supporting data sources. Research data were analyzed in addition to getting overview of the overall collaboration skills, but also to get an overview of the collaboration skills within each indicator. The average of overall students’ collaboration skills indicator is 88.9% (very good category). Indicators of Work productively, Contribute actively, Committed to completing group goals, Able to responsible, Appreciate other’s contributions, Able to control emotions, Participate respectfully in discussions, debates, and differences, Trust each group member’s strengths are in very good category, respectively: 90%, 83.3%, 83.3%, 83.3%, 100%, 100%, 99.1% and 98.3%. Meanwhile, indicators of Balance in listening and speaking, and indicators of Able to make group decisions are in good category with percentages of 73.7% and 78.5%. The best collaboration skills indicator in this study is Appreciate other’s contributions and Able to control emotions. Highschool students’ collaboration skills profile in excretion system virtual lab work is generally in very good category, where students able to work productively; many of them contribute actively; able to balance in listening and speaking; they commited to completing group goals; able to responsible; appreciate other’s contributions; able to control emotions; participate respectfully; able to trust each group member’s strengths; and able to make decisions together. In addition, the virtual lab work learning method received a positive response from students, almost all students can feel the benefits in learning, especially to practice their collaboration skills.